Family Planning Programs and Food Security in Nigeria: A Quantitative Approach - Andeskebtso Yohanna Adaki (Inclusive Society and Sustainability Studies, 2023)
The issue of food security remains a pressing global concern, particularly in emerging nations facing the challenges of rapid population expansion, constrained agricultural resources, and inadequate infrastructure. Amidst Nigeria's persistent struggles with food security aggravated by a swiftly growing population, this study undertook an examination of the efficacy of family planning interventions in ensuring sustainable food provision. A cohort of 120 participants from diverse Nigerian states participated in the study, responding to structured questionnaires. The collected data underwent SPSS software analysis, leading to tabulated data and percentages reflecting respondents' viewpoints. Through regression analysis, the study found a statistically significant relationship between the implementation of family planning programs and food security. Findings revealed that for every unit increase in the effectiveness of family planning initiatives, there was a consequential increase of 0.315 units in food security, showcasing a notably positive impact. This association, reflected by a Beta coefficient of 0.531, underscores the substantial influence of these programs on improving food security. These results highlight the potential efficacy of strategic implementation of family planning interventions as a crucial mechanism in alleviating Nigeria's food security concerns amidst rapid population growth. In response to these identified challenges, the research articulated recommendations aimed at addressing these issues. They encompassed measures like improved educational initiatives, enhanced accessibility to services, heightened public awareness campaigns, bolstered support for women, and the reinforcement of healthcare infrastructure.